Expression of angiopoietins in central nervous system hemangioblastomas is associated with cyst formation. (3rd February 2017) - Li, Xiang; Liu, Wenke; Liu, Jianping; Wang, Weiya; Zhang, Si; Chen, Jian; Hui, Xuhui
Highlights: Expression levels of Ang-1, -2 and Tie-2 in CNS hemangioblastomas are determined. Elevated Ang-2 level is discovered in cyst-associated hemangioblastomas. Anti-Ang-2 therapy may be promising for cyst-associated hemangioblastomas. Abstract: Purpose: This study aimed to determine the expression of angiopoietin-1 (Ang-1), angiopoietin-2 (Ang-2), and endothelial tyrosine kinase receptor (Tie-2) in central nervous system (CNS) hemangioblastomas (HBs) and explore the correlation with peritumoral cyst formation. Method: A total of 22 paraffin-embedded specimens derived from 11 cyst-associated and 11 solid solitary CNS HBs were collected for streptavidin-peroxidase immunohistochemical staining. The expression levels of Ang-1, Ang-2 and Tie-2 in cystic and solid HBs were estimated and compared according to the integrated optical density (IOD) of staining in the sections. To further confirm the differential expression of Ang-1 and Ang-2 between cystic and solid HBs, an additional 9 frozen specimens from 5 cyst-associated and 4 solid solitary HBs were collected for Western blot analysis. Clinical histories and radiological records of the patients were reviewed retrospectively. Results: Compared to normal cerebellum tissue, Ang-1, Ang-2 and Tie-2 were prominently overexpressed in both the stromal cells and endothelial cells of CNS HBs. The expression of Ang-2 and the ratio of Ang-2/Ang-1 in the cystic group were significantly higher than those in the solid group. The intensity of Ang-2 expression in the cystic group was negatively correlated with age. There was no correlation between the expression level of the proteins and sex, tumor location, tumor volume or cyst volume. Conclusions: Ang/Tie signaling is upregulated in HBs and is likely associated with the process of intense vascularization and cyst formation. Higher Ang-2 levels and a higher Ang-2/Ang-1 ratio may contribute to cyst formation by increasing the vascular permeability. The decrease in Ang-2 expression with advanced age in cystic-associated HBs may be associated with the reduced growth rate of peritumoral cysts among elderly patients. Ang-2 shows great potential as an effective therapeutic target of symptomatic CNS HBs associated with cysts.